Do not let your safe operating limits leave you S‐O‐L (out of luck). Issue 1 (22nd May 2020) - Stauffer, Todd; Chastain‐Knight, Denise
Abstract: Collection and utilization of process safety metrics is an important tool for driving improved safety. Tier three leading indicators (challenges to safety system) indicate failures of process safety management systems and highlight areas that should be improved to prevent a more serious event. Safe Operating Limit (SOL) exceedances are a commonly used Tier 3 leading indicator. Surprisingly, there are many different approaches used in industry to calculate safe operating limits and to apply them. This inconsistency potentially diminishes the usefulness of SOL exceedances as an effective indicator. This paper discusses current industry practices around safe operating limits as established by a recent global benchmark survey of over 150 safety practitioners. Areas explored in the survey of SOLs include; methodology for calculating, how/where information is stored, how/when established values are reviewed and audited, usage as a leading indicator, integration with operations (training, documentation), identification and tracking of when exceedances have occurred, and actions taken on exceedance. Key results and conclusions will be presented as well as recommendations on where industry should focus on improvement.